Sociability and the timing of first marriage - Odelia Heizler; Nira Yacouel; Ayal Kimhi (Institute for the Study of Labor (IZA), 2012)
This paper investigates, both theoretically and empirically, the effect of sociability on the age of marriage. Theoretically, a more sociable individual has higher chances of finding a suitable partner for marriage early in life, and hence is expected to marry earlier than an otherwise similar unsociable individual. On the other hand, a more sociable individual can afford to be more selective in choosing a mate and therefore will tend to postpone marriage until the most suitable partner is found. Using a survival model applied to Israeli data, we show that the first effect is dominant for relatively less sociable individuals, whereas the second effect is dominant for relatively more sociable individuals. Hence, people with intermediate levels of sociability will tend to marry earlier. In an era of increasing individualism and decreasing sociability, these results have important implications for marriage rates, fertility, housing markets and financial markets.
Keywords: J12; D10; 330; social networks; age of marriage; Ehe; Altersgruppe; Soziales Netzwerk; Soziale Beziehungen; Israel